Etiology and Outcome of Acute Liver Failure: Experience from a Liver Transplantation Centre in Montreal. (2002) - Tessier, Geneviève; Villeneuve, Edith; Villeneuve, Jean-Pierre
Abstract : BACKGROUND: Acute liver failure is a rare condition in which massive liver injury is associated with the rapid development of hepatic encephalopathy. Although viral hepatitis and drug-induced liver injury are the most common causes, no specific etiology is found in a substantial proportion of cases reported from Europe and the United States. AIM: To determine the etiology and outcome of patients with acute liver failure in the authors' institution. PATIENTS AND METHODS: The charts of 81 consecutive patients admitted to Saint-Luc between 1991 and 1999 were reviewed. RESULTS: The etiology was viral in 27 cases (33.2%), toxic or drug-induced in 22 (27.2%), of unknown origin in 22 (27.2%) and due to various causes in 10 (12.3%) (autoimmune, vascular, cancer). Of the 81 patients, 16% survived without liver transplantation, and 84% died or underwent liver transplantation. Survival without liver transplantation differed according to the mode of presentation: the survival rate was 27% in patients with hyperacute liver failure, 7% in those with acute liver failure and 0% in those with subacute liver failure. Among the 38 patients who underwent liver transplantation, survival one year after transplantation was 71%. In the 30 patients who died without liver transplantation, the main causes of death were cerebral edema and sepsis. CONCLUSIONS: Acute liver failure is associated with a high mortality, and liver transplantation is the treatment of choice. In a significant proportion of cases, the etiology remains undetermined and is probably related to yet unidentified hepatotropic viruses.